Vì \(\left(2x-1\right)^{2008}\ge0\forall x;\left(y-\frac{2}{5}\right)^{2008}\ge0\forall y;\left|x+y+z\right|\ge0\forall x;y;z\)
\(\Rightarrow\left(2x-1\right)^{2008}+\left(y-\frac{2}{5}\right)^{2008}+\left|x+y+z\right|\ge0\forall x;y;z\)
mà \(\left(2x-1\right)^{2008}+\left(y-\frac{2}{5}\right)^{2008}+\left|x+y+z\right|=0\)
Đẳng thức xảy ra khi \(x=\frac{1}{2};y=\frac{2}{5};z=-\frac{9}{10}\)
Vì \(\hept{\begin{cases}\left(2x-1\right)^{2008}\ge0\forall x\\\left(y-\frac{2}{5}\right)^{2008}\ge0\forall y\\\left|x+y+z\right|\ge0\forall x,y,z\end{cases}}\)
\(\Rightarrow\left(2x-1\right)^{2008}+\left(y-\frac{2}{5}\right)^{2008}+\left|x+y+z\right|=0\)
Dấu "=" xảy ra \(\Leftrightarrow\hept{\begin{cases}\left(2x-1\right)^{2008}=0\\\left(y-\frac{2}{5}\right)^{2008}=0\\\left|x+y+z\right|=0\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x=\frac{1}{2}\\y=\frac{2}{5}\\\frac{1}{2}+\frac{2}{5}+z=0\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x=\frac{1}{2}\\y=\frac{2}{5}\\z=-\frac{9}{10}\end{cases}}\)
Vậy \(\left(x,y,z\right)=\left(\frac{1}{2};\frac{2}{5};-\frac{9}{10}\right)\)
Ta có : \(\hept{\begin{cases}\left(2x-1\right)^{2008}\ge0\forall x\\\left(y-\frac{2}{5}\right)^{2008}\ge0\forall y\\\left|x+y+z\right|\ge0\forall x;y;z\end{cases}}\Rightarrow\left(2x-1\right)^{2008}+\left(y-\frac{2}{5}\right)^{2008}+\left|x+y+z\right|\ge0\)
Dấu "=" xảy ra <=> \(\hept{\begin{cases}2x-1=0\\y-\frac{2}{5}=0\\x+y+z=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x=\frac{1}{2}\\y=\frac{2}{5}\\z=-\frac{9}{10}\end{cases}}\)
Vậy x = 1/2 ; y = 2/5 ; z = -9/10